Psychopathology and coping in recently diagnosed HIV/AIDS patients - the role of gender - Benjamin O Olley; Faniswa Gxamza; Soraya Seedat; Hugo Theron; Dan J Stein; Jantjie Taljaard; Emile Reid; Helmuth Reuter (South African Journal of Psychiatry, 2004)
Background. Although there is growing literature on the psy- chological responses to and the psychopathology associated with HIV/AIDS, few investigations have focused on the role of gender. This study compared psychiatric morbidity, coping responses, and disability in male and female outpatients recently diagnosed with HIV/AIDS.